COCCIDIOSIS IN BROILER CHICKENS RAISED IN CLOSE HOUSE IN PATAS VILLAGE, GEROKGAK, BULELENG - Wayan Gede Ananta Brahmananda; I Putu Cahyadi Putra; I Made Kardena; Hapsari Mahatmi; I Nyoman Mantik Astawa (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Coccidiosis is a parasitic disease of chickens caused by the protozoan Eimeria spp. This disease economically causes many problems and losses in chicken farms, such as inhibiting growth and reducing productivity, ultimately resulting in death. Coccidiosis can attack chickens on farms that are kept with a closed-house or open-house system. Close-house farms generally have good biosecurity, but this does not rule out the possibility of a disease that attacks chickens, one of which is coccidiosis. The purpose of this case report is to report the incidence of coccidiosis in a farm with a closed-house system. The animal used as a case was a 21-day-old broiler chick from a close-house farm in Patas Village, Gerokgak, Buleleng, Bali. Clinical signs of case chickens were anorexia, dull feathers, pale wattle, weakness, separation from the flock, and faeces mixed with blood with a liquid consistency. The examination methods carried out were epidemiological investigations by calculating morbidity, mortality and case fatality rate (CFR), anatomical pathology, histopathology, parasitology (qualitative and quantitative examination of faeces), and bacteriology. The results of the epidemiological investigation consisted of morbidity of 0.5%, mortality of 0.13%, and CFR of 23%. An anatomical pathology examination found bleeding in the cecum. Histopathological examination of the cecum found haemorrhage, erosion, inflammatory cell infiltration, and schizonts in the lamina propia. Faecal examination revealed the presence of Eimeria sp. oocysts with a concentration of 234,200 oocysts/gram. Bacterial examination showed Escherichia coli growing from cecum and colon samples which are normal flora. Based on all laboratory examinations performed, the case chicken was infected by Eimeria sp. with a severe degree of infection. The advice for farmers is to improve sanitation and biosecurity to minimize the risk of contamination by coccidiosis. If sick chickens are found, treatment with antiprotozoal containing toltrazuril and diclazuril should be given.